CORPORATE GOVERNANCE DAN KINERJA LEMBAGA PERKREDITAN DESA DI KECAMATAN BLAHBATUH, GIANYAR - I Gede Cahyadi Putra; I Ketut Sunarwijaya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Good corporate governance is corporate governance that explains the relationshipbetween all interested parties in a regulated and organized business. The principles ofgood corporate governance need to be applied by Local Credit Institution managersto improve the performance of the LocalCredit Institution.This study aims to examine and obtain empirical evidence about the influence of the principles of good corporate governance which include transparency, accountability, responsibility, independence and fairness, on the performance of Local Credit Institutionin Blahbatuh District. The number of samples used in this study were 36 Local Credit Institution with 108 respondents. Determination of the sample using the saturated sample technique. The data analysis technique used is multiple linear regression. The results showed transparency, accountability, responsibility, independence and fairness had a positive effect on the performance of Local Credit Institution in Blahbatuh, Gianyar, Bali.